2013
DOI: 10.3389/fimmu.2013.00422
|View full text |Cite
|
Sign up to set email alerts
|

Functional Significance of CD57 Expression on Human NK Cells and Relevance to Disease

Abstract: Historically, human NK cells have been identified as CD3−CD56+CD16± lymphocytes. More recently it has been established that CD57 expression defines functionally discrete sub-populations of NK cells. On T cells, CD57 expression has been regarded as a marker of terminal differentiation and (perhaps wrongly) of anergy and senescence. Similarly, CD57 expression seems to identify the final stages of peripheral NK cell maturation; its expression increases with age and is associated with chronic infections, particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
215
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(230 citation statements)
references
References 122 publications
12
215
1
2
Order By: Relevance
“…47%, p = 0.0014; Figure 4C) which have been correlated with memory-like phenotype and are associated in several studies with better outcomes and improved long-term survival across many tumor types. (reviewed in 35 ) Anti-PD-L1 treated animals had very few PD-1 positive NK cells (median 2.9%, range 2.5–4.5%) and also significantly lower frequencies of PD-1 positive T cells (11% vs . 5%, p = 0.0006) (Figure 4D and E).…”
Section: Resultsmentioning
confidence: 99%
“…47%, p = 0.0014; Figure 4C) which have been correlated with memory-like phenotype and are associated in several studies with better outcomes and improved long-term survival across many tumor types. (reviewed in 35 ) Anti-PD-L1 treated animals had very few PD-1 positive NK cells (median 2.9%, range 2.5–4.5%) and also significantly lower frequencies of PD-1 positive T cells (11% vs . 5%, p = 0.0006) (Figure 4D and E).…”
Section: Resultsmentioning
confidence: 99%
“…These NK cells are functionally different than traditional, CD56 + NK cells-they are terminally differentiated and have higher cytolytic capabilities, and generally act as innate immune regulators despite being less responsive to cytokines and connected to autoimmunity and immunodeficiency (Lopez-Verges et al, 2010;Nielsen et al, 2013). Siniscalco et al (2016) examined 104 children with ASD, and found significantly lower, atypical levels of CD57 + NK cells as compared with both age-matched and adult controls.…”
Section: Immune Dysregulationmentioning
confidence: 99%
“…49 T cells are not considered to express CD57 at birth; CD57 expression increases with age and is found in 20-30% of young adults and 50-60% of the elderly (above 80 years old). 27 Levels of CD4 C , CD8 C , and CD57 C cells are also frequently increased in many cancers. 26,27,50 Expanded subsets of T cells expressing CD57 but not CD28 were highly associated with survival in our GBM patient cohort.…”
Section: Discussionmentioning
confidence: 99%
“…27 Levels of CD4 C , CD8 C , and CD57 C cells are also frequently increased in many cancers. 26,27,50 Expanded subsets of T cells expressing CD57 but not CD28 were highly associated with survival in our GBM patient cohort. All these patients were HCMV positive, as this was an inclusion criterion for the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation